Feminist fabulation : space/postmodern fiction - Barr, Marleen S. (University of Iowa Press, 1992)
The surprising and controversial thesis of Feminist Fabulation is unflinching: the postmodern canon has systematically excluded a wide range of important women's writing by dismissing it as genre fiction. Marleen Barr issues an urgent call for a corrective, for the recognition of a new meta- or supergenre of contemporary writing--feminist fabulation--which includes both acclaimed mainstream works and works which today's critics consistently ignore.